Thornless cactus: an unconventional, valuable fodder resource in arid region of India - Dev, Rahul; Dayal, Devi; M., Shamshudeen; Yadav, O. P. (Indian Farming, 2018)
Cactus pear showed great potential for increasing green fodder production in average rainfall years, and to provide a critical reserve of forage for animals in severe drought years. In droughts, cactus can also provide a source of green forage and a much-appreciated source of water for livestock. The study on evaluation of cactus in the drylands of western India revealed the high potential for growing cactus as a fodder crop. However, to capitalize the fullest potential of cactus as a fodder crop, systematic field evaluation for developing location specific production technology and feeding trials on cattle, buffalo and small ruminants are essential.